Adaptive-Contextual Differentiated Instruction in Post-Disaster Schools: Teachers’ Perceptions and Pedagogical Negotiation - Hidayati Hidayati; Dwi Priyo Utomo; Eko Susetyorini; Syafril Syafril; Dian Eka Mayasari Sri Wahyuni (Ulul Albab: Majalah Universitas Muhammadiyah Mataram, 2026)
This study aimed to analyze teachers’ perceptions of differentiated instruction, factors influencing its implementation, and forms of pedagogical negotiation emerging within the implementation of the Merdeka Curriculum in post-disaster schools in Lombok. The study employed a constructivist-interpretive paradigm using a qualitative multi-case study design involving three Sekolah Penggerak schools located in post-disaster areas. Data were collected through in-depth interviews, classroom observations, and document analysis, then analyzed thematically through within-case and cross-case analysis. The findings revealed that differentiated instruction developed adaptively and contextually rather than as a linear and procedural pedagogical practice. Teachers’ perceptions of differentiated instruction tended to be partial, pragmatic, and strongly influenced by structural limitations, school culture, pedagogical experiences, and post-disaster socio-ecological realities. The study also found that technology did not function as the primary determinant of differentiated instruction implementation, but rather as a secondary accelerator whose effectiveness depended on teachers’ pedagogical capacity. The findings resulted in the conceptual development of the Contextual Adaptive Differentiation Model (CADM), which positions differentiated instruction as an adaptively negotiated pedagogical practice shaped by contextual school realities.